2003
DOI: 10.1623/hysj.48.6.899.51425
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variation of suspended sediment load and sediment yield in an alpine catchment

Abstract: The results are described of 16 years operation of a measuring station for the automatic recording of water discharge, bed load and suspended sediment transport in the Rio Cordon catchment, a small alpine basin (5 km Les résultats indiquent que la charge en suspension correspond à 76% de la charge totale, et que la plupart du transport de matières en suspension a eu lieu lors de deux événements: une crue éclair d'été extrême en septembre 1994 (27% du total de la charge en suspension des 16 ans) et un événement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
85
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 14 publications
6
85
0
Order By: Relevance
“…in the Danube by a factor up to 2; Summer et al 1994), whereas in many cases no clear trend could be found (Zobrist et al 2004). Higher sediment discharges are usually related to high flows during snowmelt or heavy rainfall in spring, summer and autumn (Lenzi et al 2003;Margreth 2006;Asselman et al 2003). Thus, the greatest transport of fine sediments within the stream occurs in relatively short time periods (Summer et al 1994;Hamm et al 1996).…”
Section: Effects Of Land-use Change On Soil Erosionmentioning
confidence: 99%
“…in the Danube by a factor up to 2; Summer et al 1994), whereas in many cases no clear trend could be found (Zobrist et al 2004). Higher sediment discharges are usually related to high flows during snowmelt or heavy rainfall in spring, summer and autumn (Lenzi et al 2003;Margreth 2006;Asselman et al 2003). Thus, the greatest transport of fine sediments within the stream occurs in relatively short time periods (Summer et al 1994;Hamm et al 1996).…”
Section: Effects Of Land-use Change On Soil Erosionmentioning
confidence: 99%
“…Finally, suspended sediment concentrations and yields from single flood events have also been analyzed [Asti, 1999;Lenzi and Marchi, 2000;Lenzi et al, 2003]. …”
Section: Study Basins and Measuring Stationmentioning
confidence: 99%
“…During this extreme event the channel bed was the main source of sediment for bed load transport [Lenzi et al, 2003] mostly because such a large discharge was able to destroy the streambed armor layer formed over the years. Also, during the September 1994 flood, old sediment sources were reactivated and new ones were created.…”
Section: Temporal Trends In the Bed Load Transportmentioning
confidence: 99%
“…However, less is known about the hysteresis effect, production and transport of suspended sediment from small agricultural drainage basins, which can be considered as one of the most important sediment sources. From a practical point of view, it is necessary to improve understanding of the processes related to sediment dynamics at the small basin scale for modelling and prediction of suspended sediment load, mainly during single events, which are significant for the total annual sediment load (Lenzi et al, 2003).…”
Section: Introductionmentioning
confidence: 99%